Harm principle in green criminology: environmental harm and human risk matrix - Shetty, Amulya J.; Saxena, Mukul (Frontiers in Climate, 2025)
This paper proposes to bridge the gap between traditional criminal law and environmental jurisprudence by redefining the harm principle proposed by Mill through the Environmental Harm and Human Risk Matrix. The Matrix classifies environmental harm and human risk as low, medium, and high impact, creating nine intersectional approaches to assess environmental harm based on its severity and irreversibility, the risk to human and non-human wellbeing, its intergenerational impact, and the ability to mitigate the impact. Through the Matrix, the paper identifies activities that should be assessed as violations with no criminal liability, harms that should have criminal liability and harms that are subject to interpretation by the executive and the judiciary thereby helping to understand environmental harm within the socioeconomic realities of the situation. The approach not only challenges anthropocentric legal paradigms but also the interpretation of the harm principle while treating the environment as a resource. The challenge to the anthropocentric legal paradigms integrates the socioeconomic realities, environmental harm to human and non-human beings and offers guidelines to differentiate violations requiring restorative approaches from crimes necessitating punitive action. The paper further argues that if environmental harm is purely perceived from the lens of the harm principle apportioning blameworthiness based on liability, culpability and accountability, then the entire human population commits environmental harm since the environment is a resource which is used/misused by all. The paper integrates both approaches while contextualizing the use/misuse of the environment as a resource and examines liability and culpability from the profit motive, wherein environmental harm is intergenerational, pervasive, long-term, and irreversible. However, social manifestations (order, disorder and strain in the society), behavior, culture and socioeconomic vulnerabilities on the utilization of the environment as a resource are imperative to understand environmental harm before affixing accountability. The paper develops a theoretical framework examining the relevant legal and criminological theories (deterrence, rational choice, etc.) and proposes a differential approach to assess environmental harm committed for profits and those committed by the marginalized and least advantaged members of society who invariably utilize environmental resources for survival and/or out of necessity. The paper further argues that sweeping punitive actions risk creating a ‘paradox of poverty’. The Matrix contributes to the current scholarship from the legal and sociological standpoint, arguing for a just, fair and equitable utilization of resources while ensuring an inclusive and sustainable policy to combat environmental violations and thus harm. The work contributes to global green criminology discourse urging transformative legal reforms to mitigate ecological violence and advance planetary justice.